Recent advances in plant biotechnology and genetic engineering for production of secondary metabolites - Sheludko, Y.V. (Цитология и генетика, 2010)
For a long time people are using plants not only as crop cultures but also for obtaining of various chemicals. Currently plants remain one of the most important and essential sources of biologically active compounds in spite of progress in chemical or microbial synthesis. In our review we compare potentials and perspectives of modern genetic engineering approaches for pharmaceutical biotechnology and give examples of actual biotechnological systems used for production of several promising natural compounds: artemisinin, paclitaxel and scopolamine.